A new structure of phosphated superplasticiser with low sulfate sensitivity. Issue 3 (15th March 2022) - Wang, Tao; Wang, Bing; Han, Zheng; Ma, Jianfeng; Yang, Yong; Ran, Qianping
Abstract : Two small molecular dispersants (SMD-1 and SMD-2) with different charge densities of phosphate as the adsorption group were synthesised by the reaction of polyetheramine, phosphorous acid and formaldehyde. The structure and molecular weights of these two synthesised phosphated superplasticisers (PSPs) and a commercial polycarboxylate superplasticiser (PCE) were characterised by Fourier transform infrared spectroscopy and gel permeation chromatography. The dispersing, adsorption and hydration behaviours with the addition of potassium sulfate (K2 SO4 ) to the cement paste were also analysed. The experimental results showed that, compared with the conventional comb-shaped PCE, the linear structure of the PSPs provided lower dispersing ability but better fluidity retention. The addition of potassium sulfate had an obvious negative effect on the dispersing ability of PCE, while the effect on the PSPs was slight. The adsorption isotherms indicated that, with the addition of 2 wt% potassium sulfate, the competitive adsorption between sulfate ions and PCE was enhanced: the saturated adsorption of PCE decreased by 10.37%, whereas the PSPs were less affected, with the saturated adsorption of SMD-1 only decreasing by 2.32%. Isothermal calorimetry measurements showed that the PSPs showed excellent retarding ability and could delay the hydration process of cement.